Peran Pemerintah Kota Surakarta dalam Mengatasi Kekerasan terhadap Anak di Masa Pandemi Covid-19 (Studi Kasus pada Dinas Pemberdayaan Perempuan Perlindungan Anak dan Pemberdayaan Masyarakat Kota Surakarta) - Zsa Zsa Zamzami Hasri Ananda; Sri Yuliani (Program Studi Ilmu Administrasi Negara Fakultas Ilmu Sosial dan Politik Universitas Sebela, 2022)
This study aims to analyze the role of the Surakarta City government in this case the Surakarta City DPPPAPM in overcoming the problem of child abuse during the COVID- 19 pandemic. The theory used in this study is the Siagian government role theory (2005). In this study the method used is a qualitative research methoddescriptivethe data collection techniques used are interview, observation, and documentation studies. Meanwhile, the informant determination technique used is purposive sampling technique. To measure the validity of the data that has been obtained, the triangulation of sources and techniques is used. The data obtained was then analyzed using the Miles and Hubberman interactive model. The results show that the Surakarta City DPPPAPM has made efforts to overcome violence against children during the COVID-19 pandemic in accordance with the theory of the role of the Siagian government, namely as a stabilizer, innovator, modernizer, pioneer, and implementer himself. Where these efforts are carried out through efforts to prevent and handle violence against children through programs and activities through the Surakarta City DPPPAPM which are adapted to the current conditions of the COVID-19 pandemic. However, in practice there are stilllimitationsin carrying out the roleinnovatorand the implementers himself.